O15.4 Azithromycin treatment failure in women infected with genital chlamydia infection. (13th September 2015) - Hocking, JS; Vodstrcil, L; Huston, W; Timms, P; Chen, M; Bradshaw, C; Worthington, K; Lawrence, A; McIver, R; Phillips, S; Tabrizi, SN
Abstract : Introduction: Repeat infections of chlamydia are very common and may represent a new infection, re-infection from an untreated partner or treatment failure. The aim of this cohort study is to estimate the proportion of women infected with chlamydia who experience failure after treatment with 1 gram azithromycin. Methods: Women diagnosed with chlamydia were followed for 8 weeks post treatment with 1 gram azithromycin and provided weekly genital specimens for further assay. The primary outcome was the proportion of women classified as having treatment failure at least 4 weeks after recruitment. Comprehensive sexual behaviour data collection and the detection of Y chromosome DNA in vaginal swabs and genome sequencing were used to differentiate between chlamydia re-infection and treatment failure. Chlamydia culture and MIC was also undertaken. Results: There were 305 women recruited with a response rate of 66%. A total of 36 women were diagnosed with repeat chlamydia infection during follow up (11.8%; 95% CI: 8.4%, 16.0%). The median time till repeat infection was 7 weeks, with 25% of repeat infections diagnosed within 5 weeks. The risk of repeat infection increased with increasing organism load of initial infection (OR = 1.6; 95% CI: 1.2, 2.8 for each additional log increase in load). Of the 36 women with repeat infection, 16 (44.4%; 95% CI: 27.9%, 61.9%) were classified as treatment failure with an overall risk of treatment failure of 5.2% (95% CI: 3.0%, 8.4%). There was no detectable shift in MIC between initial and repeat infections with MIC within reported antimicrobial susceptibility ranges. Conclusion: Using a combination of advanced laboratory techniques and comprehensive sexual behaviour data, we estimate that about 1 in 20 women with chlamydia infection treated with 1 gram of azithromycin will fail treatment. Further laboratory investigation will determine whether there are any genomic characteristics of the infections associated with treatment failure in our cohort. Disclosure of interest statement: This study was funded by the NHMRC.